Revisiting anatomical structures of the superior orbital fissure using with interactive 3D-PDF model - Akdemir Aktaş, Hilal; Hanalioğlu, Şahin; Tunç, Osman; Tatar, İlkan (Acta Medica, 2023)
The superior orbital fissure is an important cleft that connects the orbit with the middle cranial fossa. The upper border of this fissure is formed by the lesser wing of the sphenoid bone, anterior clinoid process, and optic strut. The lower border is formed by the greater wing of the sphenoid bone. The oculomotor, trochlear, ophthalmic, abducens nerves and orbital veins pass through this small slit. The aim of this study was to review anatomical structures of the superior orbital fissure, through a 3D-PDF model that simplifies the understanding of complex anatomy of this region. According to the literature, any major artery does not pass through it, but it is closely related to the internal carotid artery. There are numerous intracranial-extracranial anastomoses around it. While extracranial branches originate from the maxillary artery, intracranial branches arise from the inferolateral trunk or the ophthalmic artery. Nerves and vascular structures related with this fissure can be damaged due to post-traumatic sphenoid fractures, infectious diseases, aneurysms, carotid-cavernous fistulas, and neoplasms. Surgeries involving the superior orbital fissure are quite complex as there are many important anatomical structures in this region. The radiological anatomy of this fissure in normal and pathological conditions is still an under-studied subject in the literature. There is a need for more detailed studies related to the superior orbital fissure enriching with anatomic models and including pathological conditions. The 3D-PDF model of the superior orbital fissure is an innovative tool to enhance the knowledge of the anatomical structures related with this region. Better understanding of this critical region is necessary to perform safe and successful surgical procedures.